96 Effectiveness of outpatient screening for the proarrhythmic effects of flecainide. (6th June 2022) - Denham, Nathan; Hall, Mark; Mahida, Saagar; Modi, Simon; Snowdon, Richard; Gupta, Dhiraj; Borbas, Zoltan; Todd, Derick; Luther, Vishal; Waktare, Johan
Abstract : Introduction: Flecainide has an established role in the treatment of common arrhythmias. The primary mechanism of action is blockade of the cardiac sodium channel, which manifests on the surface electrocardiogram (ECG) as prolongation of the PR interval and an increase in the QRS duration. The European Society of Cardiology recommends an ECG is performed within 14 days of starting therapy to screen patients for markers of proarrhythmic side effects. Our aim was to investigate the frequency of flecainide-induced arrhythmias and the role of ECG screening in contemporary practice. Methods: We performed a retrospective study of all patients either initiated on flecainide or who underwent a dose uptitration our outpatient electrophysiology service over a three-year period in. Alongside basic demographic data, we collected information on risk assessment prior to prescription including baseline ECG, imaging and ischaemia testing. We also studied the effectiveness of post-initiation ECG screening, in particular whether this was performed and whether flecainide was discontinued if: QRS duration increased by >25%, there was a new high grade atrioventricular block or bundle branch block, or a type 1 Brugada pattern. Finally, we looked at the frequency of all side effects attributed to flecainide after its prescription. Results: A total of 318 prescriptions were issued to 306 patients over the study period, of which 239 (75%) were new, 61 (19%) were an uptitration and 18 (6%) were a reinitiation of flecainide. The commonest indication was atrial fibrillation (241/318; 76%). The majority of patients underwent some form of risk assessment prior to prescribing flecainide, including echocardiography (316/318; 99%) and an ECG within the past six months (307/318; 97%). 47 patients (15%) had an assessment for ischaemic heart disease prior to prescription. Specific instructions on acquiring ECG screening of patients were documented in 80/318 (9%). The results of ECG screening are shown in figure 1. Side effects were reported in 32/318 (10%), however apart from syncope (6/318) and tachycardia (1/318), the majority were not cardiac in nature. Conclusion: Significant QRS widening or a new bundle branch block was observed in 7% however discontinuation of flecainide occurred in a minority of cases. New high grade AV block and a Brugada pattern were rare (<1%). Whilst side effects were common, only 2% were potentially cardiac in nature and no serious harm was detected. Greater awareness of a performing a post-initiation ECG is needed and the markers for pro-arrhythmia, however most discontinuations of flecainide occurred outside this window emphasising the role for ongoing follow up and ECG monitoring. Conflict of Interest: None